Survey on the situation of using penicillin antibiotics at Minh Hai General Clinic, Ca Mau province - Ho , Chấn Đông; Le , Văn Út (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Background: Penicillin is a group antibiotics. They are a subclass of beta-lactam antibiotics. Increased resistance to antibiotics is causing serious infections, complications, longer hospital stays and increased mortality. Overuse of antibiotics leads to increased risk of side effects, more requency of re-examinations, and increased drug resistance. Objective: Evaluation of penicillin antibiotic prescriptions and use at Minh Hai polyclinic, Ca Mau province. Methods: Using the cross-sectional retrospective design to collect outpatient prescriptions using penicillin antibiotics from June to September 2023 at Minh Hai General Clinic. Results: Penicillin group antibiotics were used at a rate of 72.1%, with the highest rate of Claminate. The rate of appropriate antibiotic use according to prescription is 99.67%. In particular, the penicillin group antibiotics used for patients are mostly combinations of the active ingredient amoxicillin combined with clavulanic acid. Patients coming for outpatient examination and treatment are mainly patients under 10 years old (72.85%); Female patients account for 52.98%.. Conclusion: At Minh Hai General Clinic, peinicillin was used for patients at the rate of 72.1.2%, mainly Claminate.